A physicochemical double cross-linked multifunctional hydrogel for dynamic burn wound healing: shape adaptability, injectable self-healing property and enhanced adhesion - Yuan, Yang; Shen, Shihong; Fan, Daidi (Biomaterials, 2021)
Burn wounds are one of the most destructive skin traumas that cause more than 180000 deaths each year. Patients with large, irregular burn wounds suffer from slow healing. Dynamic burn wounds have special requirements for hydrogel dressing due to their high frequency movement. To focus on dynamic burn wounds, we designed a novel double cross-linked hydrogel prepared by Schiff base and catechol-Fe3+ chelation bond. The unique double cross-linked structure of the hydrogel resulted in better physicochemical properties and enhanced efficacy. The enhanced physicochemical properties, such as faster gelation time (52 ± 2 s), stronger mechanical property (535 kPa of G’), enhanced adhesive strength (19.3 kPa) and better self-healing property, made the hydrogel suitable for dynamic wounds. The excellent shape adaptability (97.1 ± 1.3% of recovery) made the hydrogel suitable for wounds with irregular shapes. The hydrogel exhibited not only biodegradability during the wound healing process but also superior inherent antibacterial activity (100% killing ratio) and hemostatic property. The results showed that the hydrogel shortened the healing time of burn wounds to 13 days, and accelerated the reconstruction of skin structure and function. This double cross-linked multifunctional hydrogel is a promising candidate as a dynamic burn wound dressing.